Association Between Multiple Chronic Conditions and Depressive Symptoms Among Older Adults in China: Evidence From the China Health and Retirement Longitudinal Study (CHARLS) - Haixia Liu; Zhongliang Zhou; Xiaojing Fan; Chi Shen; Yang Ma; Hongwei Sun; Zhaoyang Xu (Frontiers Media S.A., 2023)
Objectives: The purpose of this study was to explore the association between multiple chronic conditions (MCCs) and depressive symptoms among older adults in China.Methods: We used the fourth round of data from the China Health and Retirement Longitudinal Study, and included 9789 older adults aged 60 years old and above.Results: Compared with the older adults without chronic disease, older adults with MCCs and those with one chronic disease had a high risk of depression (MCCs: OR-adjusted: 1.55, 95% CI: 1.37 to 1.75; one chronic disease: OR-adjusted: 1.20, 95% CI: 1.05-1.37). In urban areas, the prevalence among older adults with MCCs was 2.01 times higher than that among older adults without chronic disease (OR-adjusted: 2.01, 95% CI: 1.56-2.60), while it was 1.44 times higher in rural areas (OR-adjusted:1.44, 95% CI: 1.25-1.65). Self-reported health, duration of sleep, social activities, and type of medical insurance were the influencing factors of depressive symptoms in older adults.Conclusion: This study contributed to enriching the research on the relationship between MCCs and depressive symptoms in older adults in China.